Upaya Meningkatkan Hasil Belajar Siswa pada Tema Energi dan Perubahannya dengan Menggunakan Metode Bermain Peran di Kelas III SD Negeri 6 No. 050729 Tanjung Pura - Muamar Al Qadri; Ahmad Zaki; Suci Agustin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
This research aims to improve student learning outcomes by applying the role playing method on the theme of energy and its changes in Class III of SD Negeri 6 No. 050729 Tanjung Pura. This research explains that students' learning achievements/outcomes are still low or have not yet reached the KKM because teachers only provide or transfer teaching materials verbally and when the teacher explains, students really don't understand the material and cannot master all the material presented. The role playing method is one a learning approach that involves students in small groups which aims to activate participants actively in learning or training by directly experiencing the situation or role they play. The research used in this research is Classroom Action Research which consists of several stages including planning, action, observation and reflection using 2 cycles and involving 22 students. In the pre-cycle activities before corrective learning actions were carried out using the role-playing method, the percentage achievement obtained was 22.7%, then after corrective learning actions were carried out using the role-playing method, it increased in cycles 1 and 2. In cycle 1, students achieved a completion percentage of 77 .2% and in cycle II student gains increased significantly to 100%. From the explanation above, it can be concluded that the application of the role playing method on the theme of energy and its changes improves student learning outcomes well in Class III of SD Negeri 6 No. 050729 Tanjung Pura